1988
DOI: 10.1007/bf01728195
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulation of lymphocyteβ-adrenoceptor activity in pheochromocytoma

Abstract: The effect of an acute endogeneous catecholamine stimulation on the regulation of lymphocyte beta-adrenoceptor activity was studied in a patient with pheochromocytoma. Baseline blood pressure, heart rate, adrenoceptor density, and plasma concentrations of epinephrine, norepinephrine, and cyclic adenosine monophosphate were normal. Excessive spontaneous increases of catecholamine concentrations were accompanied by a rise in blood pressure, bradycardia, and an acute up-regulation of beta-adrenoceptors. Plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
1
1
Order By: Relevance
“…This observation is not consistent with the report of Middeke et al (24), who found a transient increase in the density of the mononuclear leukocyte ß 2 -receptors in a patient with a phaeochromocytoma within 30 min of the beginning of an acute episode of symptoms caused by a tenfold increase in the concentrations of epinephrine in plasma. However, although the sampling scheme in our study could not provide a continuous coverage of the time profile of the density of the mononuclear leukocyte ß 2 -receptors, the intervals (ca.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is not consistent with the report of Middeke et al (24), who found a transient increase in the density of the mononuclear leukocyte ß 2 -receptors in a patient with a phaeochromocytoma within 30 min of the beginning of an acute episode of symptoms caused by a tenfold increase in the concentrations of epinephrine in plasma. However, although the sampling scheme in our study could not provide a continuous coverage of the time profile of the density of the mononuclear leukocyte ß 2 -receptors, the intervals (ca.…”
Section: Discussioncontrasting
confidence: 99%
“…Two 24-hurinary collections demonstrated elevated noradrenaline (mean 315 lg/24 h, normal <80 lg/24 h) and adrenaline (mean 268 lg/24 h, normal <20 mg/24 h) levels. Blood samples, which were drawn during excessive blood pressure rise, revealed elevation of plasma catecholamines (6.793 pg/ml for adrenaline (normal 50-150 pg/ml) and 10.424 pg/ml for noradrenaline (normal 200-500 pg/ml), so that the diagnosis of pheochromocytoma was considered established. The tumor was successfully removed during laparascopic surgery.…”
Section: Sinus Node Dysfunction With Intermittent Sinus Arrest and Avmentioning
confidence: 99%
“…Hierzu zählt die Desensibilisierung von Beta-Rezeptoren, deren Empfindlichkeit erst durch eine exzessive Katecholaminausschüttung hochreguliert werden soll (10). Eine entsprechende Untersuchung der Beta-Rezeptorenaktivität ist mittels eines Lymphozytenassays möglich (10), wurde jedoch im vorliegenden Fall nicht durchgeführt.…”
Section: Diskussionunclassified